Profile of Fasting Blood Glucose and 2 Hours Post Prandial in the Elderly in Kenanga Village, Sungailiat District - Tonny Loho; Martina Rentauli Sihombing; Netalia Netalia (Jurnal MedScientiae, 2022)
Elderly is a final stage of the human life span which is characterized by physical changes and decreased body functions both anatomically, physiologically and biochemically. Changes that occur in the elderly are in the form of regulating glucose levels in the blood so that it can lead to an increase in glucose levels. The purpose of this study was to describe the profile of GDP and G2PP in the elderly in Kenanga Village, Sungailiat District. In this research, the method used is descriptive research using cross sectional technique. In this study, researchers used primary data by taking capillary blood samples from the respondent's fingers which were then measured. In this study 47.6% of the elderly had normal blood glucose levels, 26.2% of the elderly were prediabetes and 26.2% of the elderly were diabetic. Based on age, the elderly aged 60-64 years found 11.9% of the elderly with diabetes, the elderly aged 65-69 years as many as 7.1% and the elderly aged 70-74 years as much as 7.1%. 16.7% and 9.5% men who suffer from diabetes. That the prevalence of diabetes and prediabetes in Kenanga Village, Sungailiat District is not more than 50% of the existing elderly population.